2014
DOI: 10.1007/s13391-014-3164-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple AlN layers on quality of GaN films grown on Si substrates

Abstract: In this paper, we present the effect of multiple thin high-low-high-temperature AlN (HLHT AlN) nucleation layers on GaN film quality. A 1.9-µm-thick GaN film grown on Si (111) substrate shows that the multiple HLHT AlN nucleation layers have a significant effect on GaN film quality. This process also plays a very important role in the growth of GaN films on Si (111) substrates. A high quality GaN film with a uniformly faceted surface with very low dislocation densities is obtained at the optimized multiple HLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, the XRD results confirmed that the crystallinity of sample C was higher than that of sample D, which may be caused by the surface of sample D being worse than that of sample C. The surface roughness of samples C and D were 3.5 and 7.7 nm, respectively, as measured by AFM (images not shown), whereas samples A and B had surface roughnesses of 132 and 98 nm, respectively. In addition, there were no cracks on the surface of all samples were observed, even though they all were grown at very high temperatures, which usually causes cracking during cooling because of thermally induced tensile stress 7 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the XRD results confirmed that the crystallinity of sample C was higher than that of sample D, which may be caused by the surface of sample D being worse than that of sample C. The surface roughness of samples C and D were 3.5 and 7.7 nm, respectively, as measured by AFM (images not shown), whereas samples A and B had surface roughnesses of 132 and 98 nm, respectively. In addition, there were no cracks on the surface of all samples were observed, even though they all were grown at very high temperatures, which usually causes cracking during cooling because of thermally induced tensile stress 7 .…”
Section: Resultsmentioning
confidence: 95%
“…Good-quality AlN templates are crucial for obtaining high-efficiency AlGaN-based deep UV-LEDs. However, there are many difficulties in growing a thick AlN template on Si substrates: the large lattice mismatch between AlN and Si(111) (~23.4%) 6 causes high dislocation density and crack initiating stress; the presence of the native oxide layer on the Si substrate leads to low coherence between the AlN template and the Si substrate 7 8 ; AlN species with low mobility on the Si surface inhibit the structural rearrangement 9 ; and the low growth rate, which is the main problem preventing the development of AlN films on Si and sapphire substrates. Thus, the conventional growth of bulk AlN on Si substrates is a major problem for researchers.…”
mentioning
confidence: 99%
“…Aluminum nitride (AlN) on silicon (Si) is an appealing platform for semiconductor electronic and optoelectronic devices, not only for the availability of high crystalline quality Si substrates at a low cost and the dominant role of Si in modern semiconductor device technologies but also for the technical importance of AlN for a wide range of applications, such as deep-ultraviolet (UV) light emission (i.e., light emission wavelength less than 300 nm), high electron mobility transistors (HEMTs), microelectromechanical systems (MEMS), and surface acoustic wave (SAW) devices. Moreover, obtaining high-quality AlN on Si represents the first step toward III-nitride-based electronic and optoelectronic devices on Si. For example, AlN is an important buffer layer for aluminum gallium nitride (AlGaN) deep-UV light-emitting devices on Si. and it has been found that there is a direct correlation between the device performance improvement and the improvement in the AlN buffer layer quality. , …”
mentioning
confidence: 99%
“…The methods suppress the main problems arising from the differences between AlN and substrate during growth including low growth rate and lattice mismatch, which prevent the improvement of AlN templates on substrates and cause high dislocation density and crack initialing stress. For the growth of AlN on Si substrate, the presence of the native oxide layer on the Si substrate leads to low coherence between the AlN template and the Si substrate, making it difficult to obtain a smooth AlN surface1314. The crystal quality of AlN grown on flat or patterned Si substrates is still low compared with the AlN/sapphire substrate8915161718.…”
mentioning
confidence: 99%